Cognitive-Motor Interference during Walking in Older Adults with Probable Mild Cognitive Impairment - Klotzbier, Thomas J.; Schott, Nadja (Frontiers in Aging Neuroscience, 2017)
Although several studies have shown that dual-tasking (DT) mobility is impaired in Alzheimer's disease, studies on the effects of DT conditions in probable Mild Cognitive Impairment (pMCI) have not yielded unequivocal results. The objectives of the study were to (1) examine the effect of a concurrent task on a complex walking task in adults with cognitive impairment; and (2) determine whether the effect varied with different difficulty levels of the concurrent task. Furthermore, the study was designed to evaluate the Trail-Walking Test (TWT) as a potential detection tool for MCI. We examined DT performance in 42 young adults (mean age 23.9±1.98), and 43 older adults (mean age 68.2±6.42). The MoCA was used to stratify the subjects into those with and without pMCI. DT was assessed using the TWT: participants completed 5 trials each of walking along a fixed pathway, stepping on targets with increasing sequential numbers (i.e., 1-2-…-15), and increasing sequential numbers and letters (i.e., 1-A-2-B-3-…-8). Motor and cognitive DT effects (DTE) were calculated for each task. ROC curves were used to distinguish younger and healthy older adults from older adults with pMCI. The TWT showed excellent test-retest reliability across all conditions and groups (ICC :  0.83-0.97). SEM% was also low (<11%) as was the MDC95% (<30%). Within the DT conditions, the pMCI group showed significantly longer durations for all tasks regardless of the cognitive load compared to the younger and the healthy older adults. The motor DTEs were greatest for the complex condition in older adults with pMCI more so than in comparison with younger and healthy older adults. ROC analyses confirmed that only the tasks with higher cognitive load could differentiate older adults with pMCI from controls (area under the curve >.7, p<.05). The TWT is a reliable DT mobility measure in people with pMCI. However, the condition with high cognitive load is more sensitive than the condition with low cognitive load in identifying pMCI. The TWT-3 thus could serve as a screening tool for early detection of individuals with pMCI. Future studies need to determine the neural correlates for cognitive-motor interference in older adults with pMCI.